Tongue necrosis secondary to mucormycosis in a diabetic patient: A first case report in Malaysia - Fattah, S.Y.A.S.A.; Hariri, Firdaus; Ngui, Romano; Husman, S.I.S. (Elsevier Masson, 2018)
Mucormycosis is a rare fungal infection and high mortality that commonly affects patients with the weakened immune system. We present an unusual case of tongue necrosis probably due to the healthcare-associated mucormycosis (HCM) in a diabetic patient. Although cannot be proved with certainty, we surmise that intubation as a risk factor in our case. The diagnosis was confirmed by histopathological examination (HPE) of the necrotic tissue specimen. The patient was responded well to lipid complex amphotericin B (250 mg) regime after surgery. Subsequent follow up revealed that no signs of recurrence. Early, recognition, diagnosis, prompt treatment and awareness among clinician are representing the most effective way of managing the disease.